Effect of Pre-incubation Storage of Hatching Eggs on Subsequent Post-hatch Growth Performance and Carcass Quality of Broilers - Alsobayel, A.A.; AL-Miman, S.S. (International Journal of Poultry Science, 2010)
The study was conducted to assess the effect of eggs pre-incubation storage duration on post-hatch growth performance and carcass quality of broilers hatched from eggs purchased from local commercial hatchery in Riyadh area. A total of three groups of 80 one day-old, Ross meat-type chicks were used in the study. The chicks were hatched from eggs that were stored for either 1, 7 or 14 days and were randomly divided into four replicates of twenty birds, group weighed and assigned to 4 pens (1.5 m x 1 m) bedded with red sand as litter in an environmentally controlled house and grown under standard management practices. Birds in each replicate were weekly group weighed and weekly feed intake and daily mortality were recorded. Measurements were made of body weight gain, growth rate, feed intake and feed conversion at different age periods. At 5 weeks of age, 3 males and 3 females were randomly selected from each replicate, individually weighed and slaughtered after they have been fasted for 12 h and were inspected for breast blisters and foot pad lesions. Measurements were made of bird live weight, carcass weight and carcass percentage of live weight, abdominal fat weight, heart, liver and gizzard weights and their percentages of carcass weight. Results of the studies revealed that broilers produced from one day stored eggs had significantly (p<0.05) better growth performance which was reflected in higher body and carcass weights, less feed intake and better feed conversion compared with those of chicks produced from eggs stored for 7 or more days. Pre-incubation storage of hatching eggs for 7 days or more had an adverse effect on broilers’ performance, however, the adverse effect was more pronounced at early age periods and with prolonged pre-incubation storage of hatching eggs.